Unveiling the Guidelines: Women’s Dress in Hadīth and its Relevance in Indonesian Society - Fadhil, Haidar Masyhur; Imtyaz, Rizkiyatul (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
This study explores the burgeoning trend of Islamic attire (pakaian syar'i) among millennials in Indonesia. Employing a multidisciplinary approach involving text analysis and sociological perspectives, the research aims to deeply understand Muslim women's attire within Islamic tradition and its Indonesian context. The analysis begins with scrutinizing hadīths related to standards of Muslim women's clothing and the perspectives of Islamic scholars. Additionally, it uncovers that scholars universally agree on four clothing aspects: looseness, non-transparency, dissimilarity to opposite gender clothing, and covering intimate parts (‘Awrah). Moreover, the research identifies the trend of Islamic attire evolving into a religious commodity. In contemporary society, a clear divide exists between Islamic attire and general Muslim women's clothing. The discourse on Islamic attire has gained prominence, influencing both majorities and minorities. Initially a minority perspective, the Islamic attire label and its associated phenomenon are now a dominant fashion trend, sparking debates and discussions.